Onomastic aspects of the Old-Polish apocrypha analysis. Towards text, genre and discourse - Rejter, Artur (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The article concerns the possibilities of Old-Polish apocrypha analysis from onomastic perspective. The research certifies that proper names observed in contexts of text, genre and most of all discourse can bring interesting answers to a question of apocrypha character. Two main functions of proper names are distinguished: speech genre forming and fear eliciting. One can affirm that the first function is connected with structural and semantic aspects of apocrypha speech genre, whereas the second one relates to pragmatic and partly style levels of the speech genre pattern. However both functions are important in the analysis of discourse level which is significant in the case of research on apocrypha understanding as an Old-Polish culture phenomenon.